2022
DOI: 10.1155/2022/1778562
|View full text |Cite
|
Sign up to set email alerts
|

The Artificial Intelligence and Neural Network in Teaching

Abstract: This study aims to explore the application of artificial intelligence (AI) and network technology in teaching. By studying the AI-based smart classroom teaching mode and the advantages and disadvantages of network teaching using network technology and taking the mathematics classroom as an example, this study makes an intelligent analysis of the questioning link of classroom teachers in the teaching process. For the questions raised by teachers, the network classification models of convolutional neural network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A recent study showed that ChatGPT successfully revised complex patient education materials on spine surgery and joint replacement, making them readable at fifth-to sixth-grade levels [17]. Another study proposed that AI could enable educators to transition to mentorship roles by compiling the best learning strategies from top educators, allowing students to enhance their learning experiences independently and efficiently [18]. Furthermore, AI can offer personalized learning experiences tailored to individual students' needs and abilities, potentially improving engagement and knowledge retention for more effective learning.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that ChatGPT successfully revised complex patient education materials on spine surgery and joint replacement, making them readable at fifth-to sixth-grade levels [17]. Another study proposed that AI could enable educators to transition to mentorship roles by compiling the best learning strategies from top educators, allowing students to enhance their learning experiences independently and efficiently [18]. Furthermore, AI can offer personalized learning experiences tailored to individual students' needs and abilities, potentially improving engagement and knowledge retention for more effective learning.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that ChatGPT was able to revise and simplify the writing of complex patient educational materials about spine surgery and joint replacement so they were readable at the fifthto sixth-grade levels [8]. Another study suggested that educators could transition to more of a mentorship role, because AI may compile the best learning strategies from the best educators, allowing students and learners to improve their educational experiences independently and efficiently [11]. Additionally, AI can provide personalized learning experiences tailored to individual student needs and abilities.…”
Section: Discussion Of Key Findingsmentioning
confidence: 99%